2017
DOI: 10.1111/dom.13052
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of achieving postprandial glucose control using closed‐loop systems in patients with type 1 diabetes

Abstract: For patients with type 1 diabetes, closed-loop delivery systems (CLS) combining an insulin pump, a glucose sensor and a dosing algorithm allowing a dynamic hormonal infusion have been shown to improve glucose control when compared with conventional therapy. Yet, reducing glucose excursion and simplification of prandial insulin doses remain a challenge. The objective of this literature review is to examine current meal-time strategies in the context of automated delivery systems in adults and children with type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 115 publications
(201 reference statements)
1
73
0
1
Order By: Relevance
“…A recent study found a positive correlation between time‐to‐peak insulin action and HbA1c level in studies of closed‐loop insulin delivery and sensor‐augmented pump therapy, indicating the need for insulins with rapid and consistent absorption properties that are more able to reproduce physiological insulin responses . Current rapid‐acting insulin analogues (RAIAs) — insulin aspart (IAsp), insulin lispro and insulin glulisine — have faster absorption kinetics than regular human insulin; however, post‐prandial glucose (PPG) control with pump therapy remains limited by the pharmacokinetics of RAIAs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found a positive correlation between time‐to‐peak insulin action and HbA1c level in studies of closed‐loop insulin delivery and sensor‐augmented pump therapy, indicating the need for insulins with rapid and consistent absorption properties that are more able to reproduce physiological insulin responses . Current rapid‐acting insulin analogues (RAIAs) — insulin aspart (IAsp), insulin lispro and insulin glulisine — have faster absorption kinetics than regular human insulin; however, post‐prandial glucose (PPG) control with pump therapy remains limited by the pharmacokinetics of RAIAs …”
Section: Introductionmentioning
confidence: 99%
“…15 Current rapid-acting insulin analogues (RAIAs)insulin aspart (IAsp), insulin lispro and insulin glulisinehave faster absorption kinetics than regular human insulin; 16 however, post-prandial glucose (PPG) control with pump therapy remains limited by the pharmacokinetics of RAIAs. 17 A new generation of ultra-fast-acting insulins, such as BioChaperone Lispro, 18,19 treprostinil lispro 20 and fast-acting insulin aspart (faster aspart), is under development. Faster aspart is the first of these to be approved for pump use in adults with T1D and type 2 diabetes (T2D) and it is now available in several countries.…”
mentioning
confidence: 99%
“…The potential that these new rapid‐acting insulins could improve the performance of closed‐loop automated insulin delivery systems (e.g. the artificial pancreas) remains of great interest, with ongoing trials evaluating their use in this environment.…”
Section: What Is the Potential Role For The Second‐generation Of Rapimentioning
confidence: 99%
“…Understandably, several patients with T1D view eating as a stressful task, and eating disorders have a higher prevalence especially among women with T1D than in the general population [70]. Current versions of the AP perpetuate glucocentric T1D management by requiring users to enter their carbohydrate intake at every meal [8]. …”
Section: Domains Of Ethical Issuesmentioning
confidence: 99%
“…A first commercial version of the AP was approved by the FDA in September 2016 [7]. Most of the currently developed AP versions are hybrid closed-loop systems: they still require the patient to announce exercise and meals, with or without exact carbohydrate counting [8, 9]. This is partly due to the pharmacokinetics of the available insulins and equilibration between interstitial glucose measured by the continuous glucose monitoring device and actual blood glucose values.…”
Section: Introductionmentioning
confidence: 99%